Hubungan Pengetahuan Dan Sikap Pasien Tuberkulosis Dengan Pencegahan Penularan Serumah Di Puskesmas Balinggi - Ni Kadek Wiranti; Evi Setyawati; Matius Paundanan (Universitas Widya Nusantara, 2024)
Tuberculosis (TB) is a disease caused by the Mycobacterium tuberculosis microorganism and it is transmitted by droplets of saliva from TB patients and penetrates into the bronchioles or alveoli. Globally, about 10 million people are suffer from TB disease in 2019, and Indonesia has about 255,812 cases of Pulmonary Tuberculosis. In Central Sulawesi Province in 2020 about 5,741 cases of TB patients. The aim of the research was to analyze the Knowledge and Attitude of Tuberculosis Patients regarding the Prevention of Transmission in Households at the Balinggi Public Health Center, Balinggi District, Parigi Moutong Regency. This is quantitative research by using an analytical survey design with a cross-sectional approach. The total of sample was 30 patients with tuberculosis disease taken by total sampling technique. The results found that about 76.7% of respondents have good knowledge of good transmission prevention and about 70.0% of respondents have good attitudes toward good transmission prevention. Data analyzed by using the Fisher's Exact Test with p-value = 0.060, it means that have no correlation between Knowledge about Tuberculosis and Prevention in Household Transmission at the Balinggi Public Health Center, Balinggi District, Parigi Moutong Regency, and p-value = 0.003 it means that have a correlation between attitudes about Tuberculosis and Prevention in Household Transmission at the Balinggi Public Health Center, Balinggi District. Parigi Moutong Regency. Suggestions for the Balinggi Public Health Center to pay more attention to the knowledge and attitudes of tuberculosis patients in prevention transmission in the household.